Poor reading comprehension issue in EFL classroom among Indonesian secondary school students: Scrutinizing the causes, impacts and possible solutions - Nanda, Dodi Widia; Azmy, Khairul (Englisia Journal, 2020)
Reading comprehension is considered a challenging part of learning English for many Indonesian secondary school students. This study aims to explore the causes, impacts, and possible solutions for poor reading comprehension issues. The study scrutinizes the issue by reviewing previous studies, in which a number of articles and books were critically analyzed. The results indicate that poor reading comprehension occurs due to three remarkable factors, which are students’ lack of motivation, low prior knowledge, and poor English vocabulary. Moreover, this issue also leads to three main adverse impacts, such as reducing students’ learning achievement, hindering students’ problem-solving skills, and inhibiting students’ future studies and careers. Therefore, in responding to the problem above, this study proposes two learning approaches, which are the Cooperative Integrated and Reading Composition (CIRC) Technique and Metacognitive Strategy.